Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1017/s1368980010002041
|View full text |Cite
|
Sign up to set email alerts
|

CHD risk in relation to alcohol intake from categorical and open-ended dietary instruments

Abstract: Objective: To examine the risk of CHD in relation to alcohol intake from three different instruments. Design: In the European Prospective Investigation into Cancer in Norfolk study, weekly alcohol intake was estimated from a single question in a mail-in health and lifestyle questionnaire (HLQ), a semi-quantitative FFQ, and a 7 d diet diary (7DD). Information on smoking status, physical activity, disease history, social class and medication use was reported in the HLQ. Height, weight, blood pressure and blood l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…Intake of alcohol and other nutrients was then estimated by multiplying frequency of intake by reported portion size. Consistent with published reports, diet records collected on a 6% sub-sample of WHI women showed a correlation between alcohol intake estimated from the FFQ and diet record of 0.86 (21, 22). Total nonalcohol energy intake was calculated by multiplying the amount of alcohol consumed (g) by 7 (kcal/g) and subtracting this value from total energy intake (kcal).…”
Section: Methodssupporting
confidence: 88%
“…Intake of alcohol and other nutrients was then estimated by multiplying frequency of intake by reported portion size. Consistent with published reports, diet records collected on a 6% sub-sample of WHI women showed a correlation between alcohol intake estimated from the FFQ and diet record of 0.86 (21, 22). Total nonalcohol energy intake was calculated by multiplying the amount of alcohol consumed (g) by 7 (kcal/g) and subtracting this value from total energy intake (kcal).…”
Section: Methodssupporting
confidence: 88%
“…This observation corresponds to several urinary nitrogen biomarker studies (Rothenberg et al, 1993;Rothenberg, 1994;Bingham and Day, 1997;Bingham et al, , 2001Klipstein-Grobusch et al, 1998;Day et al, 2001;McKeown et al, 2001;Mahabir et al, 2006) and a pooled analysis of fibre and colorectal cancer (Dahm et al, 2010). However, evidence that 7DD and the FFQ estimates of alcohol were similarly associated with CHD, suggesting that such differences may be specific to specific nutrients rather than existing instrument-wide (Ward et al, 2010). The episodic nature of alcohol consumption, in contrast with a habitual dietary component such as fibre, may explain the contrast between the results of this study of fibre and those found for alcohol in EPIC-Norfolk (Ward et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…However, evidence that 7DD and the FFQ estimates of alcohol were similarly associated with CHD, suggesting that such differences may be specific to specific nutrients rather than existing instrument-wide (Ward et al, 2010). The episodic nature of alcohol consumption, in contrast with a habitual dietary component such as fibre, may explain the contrast between the results of this study of fibre and those found for alcohol in EPIC-Norfolk (Ward et al, 2010). To understand the extent to which heterogeneity amongst cohort study results can be attributed to differences between dietary instruments, further comparisons of diet-disease relationships analysed by multiple dietary assessment methods is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a significant negative relationship between dietary fiber consumption and risk of colorectal cancer was observed when using food records but not FFQs . In contrast, the relationship between alcohol intake and risk of coronary heart disease was found to be similar using both methods . Variation between food records and FFQs in linking fiber intake to the risk of coronary heart disease has also been shown .…”
Section: Issues In Nutritional Clinical Trials and Epidemiology Studiesmentioning
confidence: 97%